ENHANCING VITAMIN C CONTENT IN SOAP PRODUCTION VIA SUBSEQUENT AMOUNT OF EXTRACT FROM PHYLLANTHUS AMBLICA AND COSNICIUM BLUEMEANUM - Ruhana Wati Iran; Surina Nordin; Dayang Kamariah Tajul Maulok (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
The demand for cosmetic products is rapidly growing, despite the majority of them is high in chemical substances and may harm the skin. Nowadays, there are other alternatives that may help to prevent the use of chemical substances in cosmetic products. For example, fruit contains its own nutrient. Furthermore, there are some fruits that contains high in vitamins and also good for the skin. Researchers noticed that Phyllantus amblica (Melaka fruits) has an unpleasant odor but it higher with contains 30 times more vitamin C compared to orange while Cosnicium blumeanem (mengkunyit) helps raise the level of vitamins C in the body. Therefore, looking at potential and benefits, research has been conducted to produce a bar soap (Amblica Soap) from Phyllantus amblica and Cosnicium blumeanem. Analyze has been done to determine the vitamin C, antioxidant level, and perception level of respondents towards Amblica Soap. Likert Scale and High-Performance Liquid Chromatography (HPLC) was used as the quantitative instrument. A number of 30 respondents were selected based on their locality. Descriptive analysis was used to analyses collected using SPSS version 25.0. Resulting confirming that is Amblica Soap not contain in vitamin C and shows the perception level of respondents towards Amblica Soap is highly positive. In conclusion, Amblica Soap accepted optimistically.